Complications associated with oncological therapy - how to minimize? - Angelika Szczęśniak; Natalia Serwin; Ela Cecerska-Heryć; Anna Stangret; Agata Mularczyk; Konrad Grzeszczak; Katarzyna Topczewska (Kazimierz Wielki University, 2020)
During cancer therapy, patients undergo long-term treatment with chemotherapists. Unfortunately, although chemotherapy effectively destroys cancer cells, its toxicity may cause many adverse effects, weakening the patient's body. Their intensity is determined by many factors, including the age of the patient, the dose and type of drugs, the efficiency of metabolism and the occurrence of coexisting diseases. The most common side effects associated with chemotherapy include: myelosuppression, anaemia, neutropenia, thrombocytopenia, thrombocytopenia, thromboembolic disease, cardiovascular disorders, hair loss, nausea, diarrhoea, mucositis, taste change or fatigue. The complications that occur during or after chemotherapy are still a huge challenge for modern oncology. It is very important that the treatment of a patient with cancer is conducted by a team of doctors with many specializations. The individualization of treatment and the introduction of combined therapy may significantly minimize the occurrence of many serious complications, which may affect not only the quality of treatment, but also the patient life expectancy.